Analysis of macronutrient content macro nutrient content in organic fertiliser using fermented betel leaf extract - Amrullah, Shafwan; Ariskanopitasari, Ariskanopitasari; Tanggasari, Devi; Rizaldi, Lalu Heri; Mikhratunnisa, Mikhratunnisa; Radiansyah, Adi; Harjito, Harjito (Protech Biosystems Journal, 2023)
The use of organic fertilizers in Indonesia is increasing, this is due to the scarcity of synthetic fertilizers. Organic fertilizers have their own challenges in terms of the concentration they contain. In addition, some organic materials that exist today are very abundant, so it needs to be used as organic fertilizer, one of which is betel leaf. However, betel leaf itself is an additional ingredient that can increase the existing nutrient content. In this study, analysis of the macro elements in organic fertilizers was carried out by adding variations in the amount of betel leaf raw material. The research was conducted using variations of betel leaf extract 2%, 4%, and 6%. The test analysis in this study was in the form of N, P, and K levels. The results showed that the highest N content was in the 4% betel leaf variation, which was 0.1%, the highest P content was in the 2% variation, which was 0.04%, and the highest K content was at 2% variation, namely 0.066%. From these results, it can be said that there was no significant effect of the addition of betel leaf extract on the macro-nutrient content of liquid organic fertilizer.